Development and reproductive biology of the bamboo borer, Dinoderus minutus fabricius (coleoptera : bostrychidae) - Ahmad Razi, Norhisham (2012)
Infestation by the bamboo borer, Dinoderus minutus on felled culms and bamboo products is a serious problem in the bamboo industry worldwide particularly in Malaysia. However, biological studies concerning Dinoderus spp. is very scarce in spite of the great economic importance of this problem. Since bamboo is very susceptible to borers this project is conducted to examine and investigate the development and reproductive aspects of the bamboo borer, D. minutus. Developmental stages of D. minutus on bamboo block of Gigantochloa scortechinii shows a significant difference (p<0.01) in boring capacity and lifespan of adult beetle at different moisture content tested. Infestation can occur from early felling of bamboo and it became severe as moisture content decreased to 15% moisture content. Overall life cycle recorded for D. minutus from egg to adult stage in bamboo was 98.28±1.26 days. Establishment of culture on nutrient rich diet showed cassava (Manihot esculenta) as a suitable culture medium for D. minutus with continuous emergence of newly emerged beetle throughout the rearing period. Continuous emergence of newly emerged beetles started from day 90 onwards throughout the rearing period. Observation on sexual characteristics of D.minutus showed no sexual differences in adult beetle. Sexual identification was noticed in the terminal abdominal segment of pupa. Gonapophyses, comprising a pair of conical extrusions were present at the terminal abdominal segment in the female pupa whilst a pair of parameres was observed in the male. These morphological characteristics which was identified only in the pupal stage, proved to be the most reliable method to determine the sex of D. minutus. Ovipositional characteristics of D. minutus from population reared on bamboo and cassava showed no significant difference (p≥0.05) for pre-ovipositional and ovipositional period between female beetles from both culture. However, there was a significant difference (p<0.05) in total egg laid per female per lifespan. Female beetle from cassava produced higher egg per lifespan due to longer ovipositional period. Egg incubation varied from fourth to sixth day with a mean period of 5.21±0.22 days. Egg development was observed to be prominent on third day with yolk globules becoming tightly packed taking the form of larvae. Hatchability of egg was 61.5%±1.24 from 100 eggs collected. Study on larval development of D. minutus using individual rearing method on different powder-state diet resulted with highest number of succeeding instar into pupal stage in cassava flour. Five classes of head capsule were obtained indicating five moults from first instar to pupa with a mean duration of 52.8±0.31 days. There were significant difference (p<0.01) for head capsule width, larval body length and weight, and duration for different instars. Detailed information provided on the development and reproductive biology of D. minutus will serve as a basis for a deeper understanding of its biological development before proper control management can be established.